2018
DOI: 10.1080/09064702.2019.1611913
|View full text |Cite
|
Sign up to set email alerts
|

Impact of selected antioxidant vitamins (Vitamin A, E and C) and micro minerals (Zn, Se) on the antioxidant status and performance under high environmental temperature in poultry. A review

Abstract: The aim of this review was to discuss the effects of heat stress on antioxidant status and performance in poultry. Based on the recent literature data, the following conclusions can be drawn: (1) Heat stress can cause harmful effects in birds (e.g. increased ROS (Reactive Oxygen Spices) production and lipid peroxidation, decreased vitamin concentrations, changed enzyme activity) and consequently in production parameters (e.g. feed intake, body weight and feed conversion ratio). (2) Diets containing high Vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 52 publications
2
33
0
Order By: Relevance
“…Several previous studies have also reported that heat stress induces ROS in various cells types (Davidson and Schiestl, 2001; Katschinski et al, 2000). For instance, a review by Horváth and Babinszky (2018) stated that heat stress can lead to harmful impacts on birds including increase in the production of ROS, the formation of MDA as an indicator for lipid peroxidation, and decreased vitamin concentrations (Horváth and Babinszky, 2018). It has also been suggested that overproduction of ROS is caused by the reduction of mitochondrial respiratory chain activity due to heat stress (Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have also reported that heat stress induces ROS in various cells types (Davidson and Schiestl, 2001; Katschinski et al, 2000). For instance, a review by Horváth and Babinszky (2018) stated that heat stress can lead to harmful impacts on birds including increase in the production of ROS, the formation of MDA as an indicator for lipid peroxidation, and decreased vitamin concentrations (Horváth and Babinszky, 2018). It has also been suggested that overproduction of ROS is caused by the reduction of mitochondrial respiratory chain activity due to heat stress (Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In Experiment 3, various nutritional intervention strategies to reduce oxidative stress in tissue were combined and tested in a commercial relevant situation where birds were fed a corn-soy based diet with no oxidized fat but exposed to mild heat stress during the grow out period to mimic environmental conditions that could lead to oxidative stress ( Slimen et al, 2014 ; Akbarian et al, 2016 ; Lu et al, 2017 ). The harmful effects of heat stress in birds could be attributed through disruption of mitochondrial function, increased oxidative stress and lipid peroxidation, decreased vitamin levels and altered enzyme activity leading to reduced production performance ( Horváth and Babinszky, 2018 ). In this study, there were no differences ( P > 0.05) between the treatment groups with respect to live weight, or carcass weight and yield ( Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
“… Kumbhar et al (2018) reported that dietary combination of Se and Vitamin E (rather than used individually) was effective in increasing the catalase, SOD, as well as glutathione peroxidase activities thereby reducing malondialdehyde level or oxidative stress in breast muscle tissue from birds under heat stress. Horváth and Babinszky (2018) reported that high levels of vitamin A, E, C, and Zn as well as Se can support enzyme activity, reduce oxidative stress, and improve production performance in birds under heat stress. Interestingly, the antioxidant benefits from vitamins and microminerals were greater when combined in diets for birds under heat stress ( Horváth and Babinszky, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest, is the adoption of nutritional manipulations as a measure to ameliorate heat stress in poultry production. Nutritional intervention involves feed formulation to meet metabolic requirements as well as the inclusion of feed additives, such as vitamins, minerals, antioxidants, amino acids, probiotics, prebiotics, organic acids, essential oils and electrolytes (10)(11)(12)(13). These strategies are targeted at minimizing metabolic heat generation, improving water balance, electrolytes and nutrient intake, reduction in energy losses and attenuating reactive oxidative species production (5,14,8), since it has been ascertained that the initiation of heat stress is tightly associated with induction of oxidative stress (15,16).…”
Section: Introductionmentioning
confidence: 99%